Pengaruh Kemudahan Penggunaan Fintech, Self-Control, dan Gaya Hidup terhadap Pengelolaan Keuangan Pribadi Generasi Z di Bekasi pada Era Cashless Society - Devina Elga Ranjani; Christophorus Indra Wahyu Putra; Eri Bukhari; Bayu Seno Pitoyo (Jurnal Manajemen Bisnis Digital Terkini, 2026)
This study aims to analyze the influence of the ease of use of fintech, self-control, and lifestyle on the personal financial management of Generation Z in Bekasi City. A quantitative approach was used with a purposive sampling technique, involving 148 respondents of fintech users from Generation Z. Data was analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method to test the relationship between variables. The results of the study showed that the three variables had a positive and significant effect on personal financial management. The self-control variable had the strongest influence (O = 0.524; P < 0.001), followed by fintech's ease of use (O = 0.262; P < 0.001), and lifestyle (O = 0.135; P = 0.021). These findings confirm that self-control is a key factor in shaping healthy financial behaviors, while easy access to fintech services and lifestyle patterns also strengthen the effectiveness of financial management. This research makes a practical contribution to the development of financial literacy strategies that emphasize the importance of self-control, the use of financial technology, and the awareness of a balanced lifestyle. Thus, the results of the research can be the basis for educational institutions, fintech service providers, and policymakers in designing financial capacity building programs for Generation Z.